Exploring Liposome–Protein Interactions with Lauryl Dansyl as a Membrane Probe - Sandoval-Altamirano, C (John Wiley and Sons Inc, 2025)
The use of lauryl dansyl (LD) as a membrane probe to investigate interaction processes at the membrane surface is proposed, which are crucial for developing controlled drug delivery systems and designing molecules that can disrupt membranes. The Förster energy transfer process wherein the amino acid Trp in proteins transfers its energy to an acceptor (dansyl) is examined. This study includes both steady-state and time-resolved fluorescence techniques, examining the interaction with free and liposome-embedded probes. The modification of dansyl is straightforward and high throughput, making it highly attractive. Photophysical characterization of lauryl dansyl reveals solvatochromism, with bathochromic shifts in emission correlating with increasing medium polarity, allowing us to characterize the polarity of the probe environment in different membrane systems. The probe displays the anticipated affinities for liposome–protein interaction, confirming its potential use. This study provides deeper insights into how fluorophore-modified liposomes, such as those using LD, can explore and enhance the understanding of protein–membrane interactions. These findings have significant implications for the design of controlled drug delivery systems. © 2025 Wiley-VCH GmbH.